2020
DOI: 10.1111/jep.13457
|View full text |Cite
|
Sign up to set email alerts
|

Provider perceived barriers and facilitators to integrating routine outcome monitoring into practice in an urban community psychiatry clinic: A mixed‐methods quality improvement project

Abstract: Background and Aims Although mental health clinics are under increasing pressure to demonstrate value and routine outcome monitoring (ROM) has become a mandated component of care, providers have been slow to adopt ROM into practice, with some estimating that less than 20% of mental health clinicians use it consistently in the United States. This article explores perceived barriers and facilitators to integrating ROM into practice among clinicians and administrators in a large urban US community psychiatry clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 53 publications
0
7
0
3
Order By: Relevance
“…16,17 MBC may also help to identify treatment nonresponders, detect residual symptoms, and increase treatment adherence by encouraging patient participation. [18][19][20][21] Although there are recognized barriers and facilitators to implementation and scalability of MBC, 22,23 its feasibility for depression treatment in clinical settings and propensity to improve patient outcomes were demonstrated in several large trials and projects. 11,24,25 Despite these benefits, MBC continues to be underutilized in clinical practice.…”
mentioning
confidence: 99%
“…16,17 MBC may also help to identify treatment nonresponders, detect residual symptoms, and increase treatment adherence by encouraging patient participation. [18][19][20][21] Although there are recognized barriers and facilitators to implementation and scalability of MBC, 22,23 its feasibility for depression treatment in clinical settings and propensity to improve patient outcomes were demonstrated in several large trials and projects. 11,24,25 Despite these benefits, MBC continues to be underutilized in clinical practice.…”
mentioning
confidence: 99%
“…Although 56 out of 98 (57%) service providers responded that the online system was less time-consuming than were previous paper-based methods, only 31 out of 98 (31%) responded that the system did not increase their workload. One of the main barriers identified in previous literature to the utilization of ROM has been the significant time burden involved, and it has been suggested that software systems may alleviate some of the burden [ 5 , 12 , 35 , 36 ]. The results of the current study, with 58% (56/98) of service providers responding that the online system was less time-consuming, show promise for improvement in ROM utilization if an online system is adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Estos se agrupan en: obstáculos relacionados con los sistemas usados para la MRR, obstáculos relacionados con las personas y obstáculos organizativos. Prever estos desafíos en la implementación constituye la principal herramienta para asegurar el uso fructífero de la MRR (Barkham et al, 2023;Lewis et al, 2019;Van Wert et al, 2021).…”
Section: Utilidad De La Mrr En Psicoterapiaunclassified